Handbook of sinc numerical methods - Stenger, Frank (Boca Raton : CRC Press, 2010)
'This handbook is essential for solving numerical problems in mathematics, computer science, and engineering. The methods presented are similar to finite elements but more adept at solving analytic problems with singularities over irregularly shaped yet analytically described regions. The author makes sinc methods accessible to potential users by limiting details as to how or why these methods work. From calculus to partial differential and integral equations, the book can be used to approximate almost every type of operation. It includes more than 470 MATLABʼ programs, along with a CD-ROM containing these programs for ease of use'--
Book is accompained by one CD, entittled'Handbook of sinc methods' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references and index.
Keywords: Galerkin methods; Differential equations -- Numerical solutions